Application of Ice Breaking Strategy in Increasing the Learning Motivation of Grade III Students at SD Negeri 66 Bengkulu City - Deka Fachrozi, Ahmad; Wiwinda, Wiwinda; Aziz Bin Mustamin, Abdul (Jurnal Pendidikan dan Profesi Keguruan, 2026)
This study aimed to describe the implementation of the ice-breaking strategy to enhance the learning motivation of third-grade students at SD Negeri 66 Bengkulu City. This study was motivated by the challenges teachers face in maintaining students’ attention during long lessons, particularly when boredom arises after recess. Employing a qualitative descriptive approach, data were collected through classroom observations, interviews, and documentation involving one teacher and eight students. The findings revealed that the application of the ice-breaking strategy significantly increased students’ motivation and participation, improved classroom dynamics, and reduced boredom. Active student engagement rose from 35% to 85% after the intervention, and students were able to maintain their focus for up to 40 minutes. Teachers reported that ice-breaking activities helped create a positive and enjoyable learning environment that fostered social interaction and enthusiasm for learning. However, constraints such as limited time and insufficient variation of activities hindered optimal implementation of the program. Overall, the study concludes that ice-breaking serves as an effective pedagogical tool for enhancing learning motivation and fostering a conducive classroom atmosphere in elementary education.